MANAJEMEN MUTU DAN JAMINAN MUTU SEKOLAH UNGGUL - Hasanah, Muwahidah Nur (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
A superior school is a school developed to achieve educational excellence, the term superior is also called favorite, model, model and plus. The actual flagship school, is a school that was built jointly by all school members, not only by the authorities of education. Excellence can be achieved if all school resources are utilized optimally.